Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1741-7015-11-227
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a population-based HPV vaccination program on cervical abnormalities: a data linkage study

Abstract: BackgroundAustralia was one of the first countries to introduce a publicly funded national human papillomavirus (HPV) vaccination program that commenced in April 2007, using the quadrivalent HPV vaccine targeting 12- to 13-year-old girls on an ongoing basis. Two-year catch-up programs were offered to 14- to 17- year-old girls in schools and 18- to 26-year-old women in community-based settings. We present data from the school-based program on population-level vaccine effectiveness against cervical abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
197
2
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(224 citation statements)
references
References 24 publications
7
197
2
8
Order By: Relevance
“…Our results of vaccine impact are generally consistent with previous research on cervical dysplasia. [17][18][19][20] Although all observational studies have reported more conservative estimates than randomized controlled trials, 7 this is not surprising given that trials estimated treatment effects under ideal conditions. This does, however, highlight the importance of observational studies in determining the real-world effectiveness of this vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results of vaccine impact are generally consistent with previous research on cervical dysplasia. [17][18][19][20] Although all observational studies have reported more conservative estimates than randomized controlled trials, 7 this is not surprising given that trials estimated treatment effects under ideal conditions. This does, however, highlight the importance of observational studies in determining the real-world effectiveness of this vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low vaccine coverage may jeopardize the expected public health benefits and cost-effectiveness of qHPV vaccine programs. As there are currently few studies on the real-world effects of the qHPV vaccine [17][18][19][20][21] and none on the population-level impact of qHPV vaccine programs on the burden of disease, we undertook a populationbased, retrospective cohort study to assess the impact of the qHPV vaccine and Ontario's qHPV vaccination program on the incidence of cervical dysplasia and AGW among adolescent girls.…”
Section: What This Study Addsmentioning
confidence: 99%
“…It is important that clinicians strongly recommend vaccination of all adolescents at 11-12 y old and clearly explain to parents the necessity of protecting their teens well before potential HPV exposure, as this would result in greatest vaccine effectiveness. 35 Furthermore, vaccination of young adolescents induces higher antibody levels than vaccination at older ages. 36 Findings from the current analysis indicate parents whose teens received at least one dose of HPV vaccine were more likely to report agreement with statements about HPV vaccine safety and efficacy against a variety of health outcomes than parents of unvaccinated teens, and parents of unvaccinated teens who intended to vaccinate them in the future were more likely than parents who stated their teens would never be vaccinated to endorse these statements.…”
Section: ããmentioning
confidence: 99%
“…24 Our observed safety findings are also similar to that of other studies, whereby vaccine recipients have higher rates of injection site pain, erythema and swelling, but similar rates of systemic AEs. 32 Given the high vaccine efficacy seen in the clinical trials, and the fact that in the 8 y since its original licensure, the qHPV vaccine has been shown to be highly effective at the population level, with marked reductions in the prevalence of HPV vaccine-type related infection and disease in many countries, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] our findings suggest the vaccine should be equally effective in sub-Saharan African women.…”
mentioning
confidence: 99%